Communication Apprehension, Willingness to Communicate, and Communication Competence: A General Review - Zulida Abdul Kadir; Nurul ‘Ain Othman; Iza Nurhidayah Ismail (Development in Language Studies, 2025)
This paper explores the interrelated concepts of communication apprehension (CA), willingness to communicate (WTC), and communication competence, providing a general review of their dynamics and implications. The relationship among these concepts is cyclical and interdependent. People with high levels of CA tend to reduce WTC. Conversely, lower levels of CA often stimulate higher WTC, promote individuals to engage more freely in interactions, thus leading to better competence. Communication competence, in turn, builds confidence and reduces anxiety, strengthening the individual’s readiness to communicate.